Monologue Speech in a Foreign Language Lesson - Abishova G. (International Journal on Integrated Education, 2022)
This article discusses the issue of monologue speech in foreign language lessons, gives characteristics to monologue speech, and provides the opinions of well-known methodologists on this topic, the purpose of teaching monologue.